A new record of Frullanoides tristis (Marchantiophyta: Lejeuneaceae) from Thailand - Jian Wang (2018)
Frullanoides tristis (Steph.) van Slageren, previously known from America, Africa and Asia, is reported here as a new generic record for the Thai bryoflora. This species is well characterized as a paroicous plant, with broadly ovate to ovate-oblong lobule with 6-9 teeth and each tooth 2-3 cells long, broadly ovate to suborbicular underleaves and the base with small to medium sized ears, and with the keel of female bract with an elliptic to long and narrow wing. A complete description and illustrations of F. tristis are provided.